Conditional survival after nephrectomy for renal cell carcinoma (RCC): changes in future survival probability over time. (28th May 2013) - Bianchi, Marco; Becker, Andreas; Hansen, Jens; Trinh, Quoc‐Dien; Tian, Zhe; Abdollah, Firas; Briganti, Alberto; Shariat, Shahrokh F.; Perrotte, Paul; Montorsi, Francesco; Karakiewicz, Pierre I.; Sun, Maxine
<x xml:space="preserve">Abstract</x> Objective To examine the impact of length of survival on future survival probability, otherwise known as the effect of conditional survival (CS), after nephrectomy (NT) in patients diagnosed with renal cell carcinoma (RCC). Patients and Methods Overall, 42 090 patients with RCC who underwent NT were abstracted from the Surveillance, Epidemiology, and End Results database (1988–2008). Based on cumulative survival estimates, CS rates were derived according to patient and disease characteristics. Separate multivariable Cox regression analyses were performed for the prediction of cancer‐specific mortality (CSM), according to 1‐, 2‐, 3‐, 4‐ and 5‐year survival postoperatively. Results Immediately after surgery, the 5‐year cancer‐specific survival rate was 83.5%. Amongst patients who survived ≥1, ≥2, ≥3, ≥4, and ≥5 years after NT, the probability rates for surviving an additional 5 years were 87.0, 89.6, 90.9, 92.0 and 92.3%, respectively. Provided that patients survived 1 and 2 years after NT, the probability of being CSM‐free for another 5 years increased by +4.1 and 4.3% for stage III and +12.9 and 10.3% for stage IV disease, respectively. Similar observations were recorded for patient age, grade, nodal stage and tumour size, and were confirmed upon multivariable analyses. Conclusion Survival probabilities vary according to length of survival after NT. Specifically, even amongst patients with more advanced disease at surgery, a more favourable prognosis can be achieved after surviving for 1–2 years.